Sodium Oxide Cathodes: Insights into the Enhanced Cycle and Rate Performances of the F‐Substituted P2‐Type Oxide Cathodes for Sodium‐Ion Batteries (Adv. Energy Mater. 19/2020). Issue 19 (19th May 2020) - Liu, Kai; Tan, Susheng; Moon, Jisue; Jafta, Charl J.; Li, Cheng; Kobayashi, Takeshi; Lyu, Hailong; Bridges, Craig A.; Men, Shuang; Guo, Wei; Sun, Yifan; Zhang, Jinli; et al.
Abstract : In article number 2000135, Jinli Zhang, Xiao‐Guang Sun, Sheng Dai and co‐workers report a F‐substitution strategy for a P2‐type sodium oxide cathode (Na2/3 Ni1/3 Mn2/3 O2− x F x ), which not only enhances its Na + diffusion coefficients and specific discharge capacity, but also improves its long‐term cycling stability by suppression of the biphasic reaction in the low voltage range.